Phase change thermal interface material with interface adaptability and preparation method thereof

Through the dynamic cross-linking of stearic acid and polyolefin elastomer and the combination of thermally conductive fillers, a phase-change thermal interface material with interface adaptability and self-healing properties is formed, which solves the heat of traditional thermal interface materials in high-power electronic devices. Inadequate management problems have achieved more efficient thermal conductivity and self-repair performance.

CN119119671APending Publication Date: 2024-12-13GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411250284.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional thermal interface materials cannot meet the growing thermal management needs of modern electronic devices, especially in high power and high temperature environments, where polymer-based thermal interface materials have low thermal conductivity and lack interfacial adaptability and self-healing capabilities.

Method used

Stearic acid is used as a phase change matrix to dynamically reversibly cross-link with polyolefin elastomer to form a phase change thermal interface material with shape memory function and interface adaptability, through the introduction of boron ester bonds and thermal fillers (such as carbon fiber and aluminum nitride ) Improve the thermal conductivity and self-healing ability of the material.

Benefits of technology

Effectively alleviate the high heat flow impact problem of electronic devices, reduce contact thermal resistance, improve the plasticity and self-healing performance of materials, enhance their stability and adaptability at high temperatures, and are suitable for thermal management of high-power electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119671A_ABST
    Figure CN119119671A_ABST
Patent Text Reader

Abstract

The invention discloses a phase change thermal interface material with interface adaptability and a preparation method thereof. The phase-change thermal interface material with interface adaptability is prepared from the following raw materials: a phase-change matrix premix, a grafting agent, a cross-linking agent, an initiator and a heat-conducting filler, the phase-change matrix premix comprises stearic acid and a polyolefin elastomer, the mass ratio of the stearic acid to the polyolefin elastomer is (6-8): (2-4), and the grafting agent is a crosslinking agent. The grafting agent is borane dioxide maleimide, and the cross-linking agent is diborane dioxide. The phase change material stearic acid is added into the thermal interface material, the problem of instantaneous high heat flux thermal shock caused by high heat flux to an electronic device can be effectively relieved through instantaneous heat absorption during solid-liquid phase change of the stearic acid, and the modulus of the phase change thermal interface material is reduced through solid-liquid phase conversion; therefore, the contact thermal resistance between a heat source and the radiator can be reduced to the greatest extent in the mechanical installation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the technical field of phase change materials, and in particular to a phase change thermal interface material with interface adaptability and a preparation method thereof. Background technology:

[0002] With the rapid growth of computing demand, electronic devices are also being highly integrated at an ultra-fast speed, which brings about the problem that the power and temperature of electronic devices are constantly rising. Efficient thermal management technology has become a key link in ensuring the stable operation and extending the service life of electronic devices. Although traditional thermal interface materials have improved in heat dissipation performance, they still cannot meet the growing thermal management needs of modern electronic devices.

[0003] Among various thermal interface materials, polymer thermal interface materials are widely used in thermal control systems of electronic devices due to their advantages such as light weight, easy processing and chemical corrosion resistance. In order to maintain good interface adaptability and material flexibility, most polymer bases use elastic materials such as high-density polyethylene (HDPE), epoxy resin, butadiene triblock copolymer (SBS), polyolefin elastomer (POE), etc. as supporting materials. However, defects such as chain entanglement, voids and impurities in the polymer matrix lead to aggravated phonon scattering, so the thermal conductivity of the polymer matrix is ​​low (0.1-0.3Wm -1 K -1 ). In recent years, most of the research on high thermal conductivity polymer thermal interface materials has focused on improving the thermal conductivity of materials, while research on the adaptability of the contact interface of electronic devices and the local hot spot problems of electronic devices is relatively scarce. Thermal interface materials with excellent performance are the key to reducing the contact thermal resistance of electronic device interfaces.

[0004] In recent years, phase change thermal interface materials have gradually attracted widespread attention from researchers due to their excellent thermal conductivity and phase change latent heat. Phase change thermal interface materials will undergo a change in physical state (for example, from solid to liquid) when absorbing and releasing heat. This phase change process can effectively alleviate the high temperature heat generated by electronic devices during operation and keep the devices running within a suitable temperature range. In addition, phase change thermal interface materials have good flexibility and plasticity, which can better fill the microscopic unevenness of the interface and improve the thermal interface conduction efficiency. Therefore, the research and development of high-performance phase change thermal interface materials has become an important direction to meet the thermal management challenges of high-power and high-temperature electronic devices in the future. Summary of the invention:

[0005] The present invention solves the problems existing in the prior art and provides a phase change thermal interface material with interface adaptability and a preparation method thereof. The present invention adds stearic acid (SA) as a phase change material to the thermal interface material and utilizes the instantaneous heat absorption energy of stearic acid during solid-liquid phase change to effectively alleviate the instantaneous high heat flux thermal shock problem caused by high heat flux to electronic devices. The solid-liquid phase conversion reduces the modulus of the phase change thermal interface material, so that the contact thermal resistance between the heat source and the heat sink can be minimized during the mechanical installation process.

[0006] The purpose of the present invention is to provide a phase change thermal interface material with interface adaptability, which is prepared from the following raw materials: a phase change matrix premix, a grafting agent, a crosslinking agent, an initiator and a thermally conductive filler, wherein the phase change matrix premix comprises stearic acid and a polyolefin elastomer, the mass ratio of stearic acid to the polyolefin elastomer is 6-8:2-4, the grafting agent is dioxyborane maleimide, and the crosslinking agent is bisdioxyborane.

[0007] The phase-change thermal interface material proposed in the present invention dynamically and reversibly cross-links a polyolefin elastomer with a CC long chain and stearic acid by introducing a boron ester bond. The phase-change thermal interface material proposed in the present invention has shape memory function, good interface adaptability and self-healing properties. When the material reaches the phase change point of stearic acid, the 3D network formed by the grafting and cross-linking of chemical bonds restricts the flow of the phase-change material, and the melting of stearic acid reduces the modulus of the phase-change thermal interface material, so that the material has good plasticity and better adapts to the shape of the thermal interface. Self-healing refers to the ability of a material to repair damage through its own chemical reaction or physical reorganization after being damaged. This ability depends to a large extent on the dynamic chemical bonds inside the material. For example, in the cross-linked network of dioxyborane maleimide and bis-dioxyborane, the cross-linking bonds can be broken and reformed under heat or other external stimuli, thereby achieving self-healing.

[0008] Stearic acid is the phase change matrix in phase change thermal interface materials. As a commonly used phase change material, stearic acid is easy to flow at high temperatures. By forming a three-dimensional cross-linked structure, the fluidity of stearic acid can be effectively restricted. The cross-linked network can provide structural stability, prevent the flow and leakage of stearic acid at high temperatures, thereby maintaining the overall performance and shape of the material.

[0009] Preferably, the phase change matrix premix comprises 100 parts, a grafting agent 1-5 parts, a crosslinking agent 0.6-3.0 parts and an initiator 0.1-0.5 parts by weight. The initiator is dicumyl peroxide.

[0010] Preferably, the melting point of the polyolefin elastomer is 1.0 g / 10 min (190° C., 2.16 kg).

[0011] Preferably, the mass ratio of stearic acid to polyolefin elastomer is 7:3.

[0012] Preferably, based on the total volume of the phase change matrix premix, the grafting agent, the crosslinking agent and the initiator, the volume of the thermal conductive filler is 0-40 vol% of the total volume. More preferably, the volume of the thermal conductive filler is 10-30 vol% of the total volume.

[0013] Preferably, the thermally conductive filler comprises carbon fiber and aluminum nitride, and the volume fraction ratio of the carbon fiber to the aluminum nitride is 4:1.

[0014] More preferably, the average length of the carbon fiber is 150 μm, and the average diameter is 7 μm; the average diameter of the aluminum nitride is 1 μm.

[0015] Preferably, the dioxyborane maleimide is prepared by reacting maleic anhydride, furan, 3-amino-1,2-propanediol (APO) and phenylboronic acid.

[0016] Dioxyborane maleimide is prepared by the following steps: a mixture of furan, maleic anhydride and ethyl acetate is magnetically stirred at room temperature at a speed of 350-500r / min for 18-24 hours, and then the colorless crystals are removed by suction filtration, and the precipitate is washed three times with ether and dried under vacuum for 5-10 hours to obtain furan-A. Furan-A and ethanol are added to a three-necked flask to form solution one, and 3-amino-1,2-propanediol (APO) and ethanol are added to form solution two. Solution two is slowly dripped into the furan-A solution with a peristaltic pump, and the dripping is completed under mechanical stirring for 2-5 hours, and the temperature is maintained at about -10℃-10℃. The obtained mixture is condensed and refluxed at 85℃-100℃ for 5-10 hours. After the reaction is completed, the solution is cooled overnight, and the crystalline product is removed by suction filtration and recorded as DHPM-A. DHPM-A and toluene are added together in a three-necked flask with a mechanical stirring rod, filled with nitrogen, and refluxed at 120℃-150℃ for 7-10h; after the reaction is completed, cool overnight, and then filter and wash with petroleum ether to obtain a white product DHPM. DHPM, phenylboric acid and toluene are added together in a flask at 130℃-150℃, condensed, collected and refluxed. After the reaction is completed, the solvent is removed from the mixture under rotary evaporation conditions, and the obtained mixture is dissolved in an appropriate amount of ethanol, cooled overnight, and a white crystalline product DHPM (dioxyborane maleimide) is obtained.

[0017] Preferably, the cross-linking agent is bisdioxyborane, which is prepared by reacting benzene-1,4-diboric acid and 1,2-propylene glycol. The bisdioxyborane is prepared by the following steps: adding benzene-1,4-diboric acid and 1,2-propylene glycol to a mixed solvent of tetrahydrofuran and water, then adding magnesium sulfate, and reacting at room temperature to obtain the bisdioxyborane.

[0018] The diborane is prepared by the following steps: benzene-1,4-diboric acid and 1,2-propylene glycol are added to a mixed solvent of THF and water, and then MgSO4 is added. After standing at room temperature for 24 hours, the reaction is completed and the MgSO4 is filtered out and concentrated under reduced pressure by rotary evaporation to obtain a slightly yellow solid. The solid is then immersed in heptane, stirred at 50°C-80°C for 1-3 hours, filtered out to remove insoluble matter, and then the solvent is removed by rotary evaporation to obtain a white solid product.

[0019] The present invention also protects a method for preparing the phase-change thermal interface material with interface adaptability, comprising the following steps:

[0020] (1) adding the dried thermal conductive filler into a reaction container for premixing;

[0021] (2) adding stearic acid and polyolefin elastomer to the premixed thermal conductive filler, heating and premixing, and stirring;

[0022] (3) Adding an initiator, a grafting agent and a cross-linking agent into the reaction container in sequence, and obtaining a phase change thermal interface material after complete reaction.

[0023] Preferably, the conditions for heating premixing in step (2) are: heating temperature 150°C-170°C, rotation speed 140-160r / min, and premixing time 30-80min. More preferably, the conditions for heating premixing in step (2) are: heating temperature 160°C, rotation speed 150r / min, and premixing time 40min.

[0024] Preferably, the reaction conditions of step (3) are: reaction temperature 150°C-200°C, reaction time 18-22 min. More preferably, the reaction temperature is 170°C, and the reaction time is 20 min.

[0025] The phase-change thermal interface material proposed in the present invention has good self-repairing ability in a thermal environment and has certain interface adaptability, which provides a guarantee for the permanent packaging of small electronic devices.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] In the present invention, a polyolefin elastomer with a CC long chain and stearic acid are dynamically reversibly cross-linked by introducing a boron ester bond. When the material reaches the phase transition point of stearic acid, the 3D network formed by the graft cross-linking of the chemical bonds limits the flow of the phase change material, and the melting of stearic acid reduces the modulus of the phase change thermal interface material, so that the material has good plasticity and better adapts to the shape of the thermal interface. Moreover, by adding the phase change material stearic acid, when the chip is packaged, it is solid and easy to operate, and when the chip is working, the phase change material undergoes a phase change, which can have good interface adaptability and achieve the effect of a welding type thermal interface material, and when the temperature rises to the phase transition temperature of the phase change material, the phase change material will absorb the part of the heat released by the electronic chip due to the temperature increase, and alleviate the influence of the heat flow shock generated by the high-power operation of the electronic device on the chip performance. The addition of thermal conductive fillers carbon fiber and aluminum nitride also makes the phase change thermal interface material have good heat dissipation performance, and has certain application potential in the thermal management of electronic devices. Description of the drawings:

[0028] Figure 1 is a thermogravimetric analysis diagram of the phase change thermal interface material obtained in Examples 1-5 and Comparative Example 1;

[0029] Figure 2 is a DSC data graph of the phase change thermal interface material obtained in Examples 1-5 and Comparative Example 1;

[0030] Figure 3 This is a leakage rate test diagram of the phase change thermal interface material obtained in Example 1;

[0031] Figure 4 is a leakage rate test graph of the phase change thermal interface material obtained in Example 1-5;

[0032] Figure 5 Schematic diagram of the self-repairing performance of the phase change thermal interface material obtained in Example 1 and the load-bearing performance after repair;

[0033] Figure 6 The tensile properties of the phase change thermal interface material obtained in Example 1 at 25°C and 70°C.

[0034] Figure 7 It is a schematic diagram of the thermal conductivity of the phase change thermal interface obtained in Example 1 and Comparative Examples 1-3.

[0035] Figure 8 This is the coin printing model of Example 1. Specific implementation method:

[0036] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.

[0037] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.

[0038] A phase-change thermal interface material with interface adaptability is prepared from the following raw materials: a phase-change matrix premix, a grafting agent, a crosslinking agent, an initiator and a thermally conductive filler, the phase-change matrix premix comprises stearic acid and a polyolefin elastomer, the mass ratio of stearic acid to the polyolefin elastomer is 6-8:2-4, the grafting agent is dioxyborane maleimide, and the crosslinking agent is bisdioxyborane.

[0039] The following preferred embodiments include, by weight, 100 parts of the phase change matrix premix, 1-5 parts of the grafting agent, 0.6-3.0 parts of the crosslinking agent, and 0.1-0.5 parts of the initiator. The mass ratio of stearic acid to polyolefin elastomer is 7:3.

[0040] The phase-change thermal interface material proposed in the present invention dynamically and reversibly cross-links a polyolefin elastomer with a CC long chain and stearic acid by introducing a boron ester bond. When the material reaches the phase change point of stearic acid, the 3D network formed by the grafting and cross-linking of chemical bonds restricts the flow of the phase-change material, and the melting of stearic acid reduces the modulus of the phase-change thermal interface material, so that the material has good plasticity and better adapts to the shape of the thermal interface. Therefore, the phase-change thermal interface material proposed in the present invention has shape memory function, good interface adaptability and self-healing properties.

[0041] In the following embodiments, the melt index of the polyolefin elastomer is preferably 1.0 g / 10 min (190° C., 2.16 kg).

[0042] Dioxaborane maleimide can react with specific sites on the polymer chain to form stable chemical bonds. This process is called grafting, which can introduce functional groups into the polymer chain, thus giving the material new properties. Bisdioxaborane is a substance that can form chemical crosslinks between polymer chains. Through the crosslinking reaction, chemical bonds can be formed between different polymer chains to build a three-dimensional crosslinked network structure. The three-dimensional crosslinked structure refers to the different polymer chains connected together by chemical bonds to form a stable three-dimensional network structure. Such a structure can significantly improve the mechanical strength, thermal stability and chemical stability of the material.

[0043] Stearic acid is a commonly used phase change material, but it tends to flow at high temperatures. By forming a three-dimensional cross-linked structure, the fluidity of stearic acid can be effectively restricted. The cross-linked network can provide structural stability, preventing the flow and leakage of stearic acid at high temperatures, thereby maintaining the overall performance and shape of the material.

[0044] Self-healing refers to the ability of a material to repair damage through its own chemical reaction or physical reorganization after being damaged. This ability depends largely on the dynamic chemical bonds within the material. For example, in the cross-linked network of dioxaborane maleimide and bisdioxaborane, the cross-linking bonds can be broken and reformed under heat or other external stimuli, thereby achieving self-healing.

[0045] In the following preferred embodiments, based on the total volume of the phase change matrix premix, the grafting agent, the crosslinking agent and the initiator, the volume of the thermal conductive filler is 0-40 vol% of the total volume. Further preferably, the volume of the thermal conductive filler is 10-30 vol% of the total volume; the thermal conductive filler includes carbon fiber and aluminum nitride, and the volume ratio of carbon fiber to aluminum nitride is 4:1. The average length of the carbon fiber is 150 μm, and the average diameter is 7 μm; the average diameter of the aluminum nitride is 1 μm.

[0046] The following preferred embodiment, dioxyborane maleimide is prepared by the following steps: furan (37g), maleic anhydride (40g) and ethyl acetate (50mL) are added to a round-bottom flask. The reaction mixture is magnetically stirred at room temperature at a speed of 200-350r / min for 18-24 hours, and then the colorless crystals are removed by suction filtration, and the precipitate is washed three times with ether to obtain a light yellow product furan-a. Furan-A (40g) and ethanol (60mL) are added to a three-necked flask to form solution one, and 3-amino-1,2-propanediol (APO, 22.6g) and ethanol (16mL) are prepared into solution two. Solution two is slowly dripped into the furan-A solution with a peristaltic pump, and the dripping is completed in 2-5 hours under mechanical stirring, and the temperature is maintained at about -10℃-10℃. The obtained mixture is condensed and refluxed at 85℃-100℃ for 5-10 hours. After the reaction is completed, the solution is cooled overnight, and the crystalline product is removed by suction filtration and recorded as DHPM-A. DHPM-A and toluene are added together in a three-necked flask with a mechanical stirring rod, filled with nitrogen, and refluxed at 120℃-150℃ for 7-10h; after the reaction is completed, it is cooled overnight, and then filtered and washed with petroleum ether to obtain a white product DHPM. DHPM (5.5g) and phenylboric acid (2.8g) are added to toluene together in a flask and condensed at 130℃-150℃, collected water and refluxed. After the reaction is completed, the mixture is removed from the solvent under rotary evaporation conditions, and the obtained mixture is dissolved in an appropriate amount of ethanol, cooled overnight, and a white crystalline product DHPM is obtained.

[0047] In the following preferred embodiments, the bis(dioxyborane) is prepared by reacting benzene-1,4-diboric acid and 1,2-propylene glycol.

[0048] The diborane is prepared by the following steps: benzene-1,4-diboric acid (3 g) and 1,2-propylene glycol (2.82 g) are added to a mixed solvent of THF and water, and then MgSO4 is added. After standing at room temperature for 24 hours, the reaction is completed and filtered to remove MgSO4, and then concentrated under reduced pressure by rotary evaporation to obtain a slightly yellow solid. The solid is then immersed in heptane, stirred at 50°C-80°C for 1-3 hours, filtered to remove insoluble matter, and then the solvent is removed by rotary evaporation to obtain a white solid product.

[0049] A method for preparing a phase-change thermal interface material with interface adaptability comprises the following steps:

[0050] (1) adding the dried thermal conductive filler into a reaction container for premixing;

[0051] (2) adding stearic acid and polyolefin elastomer to the premixed thermal conductive filler, heating and premixing, and stirring;

[0052] (3) Adding an initiator, a grafting agent and a cross-linking agent into the reaction container in sequence, and obtaining a phase change thermal interface material after complete reaction.

[0053] In the following preferred embodiments, the conditions for heating premixing in step (2) are: heating temperature 150°C-170°C, rotation speed 140-160r / min, and premixing time 30-80min. Further preferred, the conditions for heating premixing in step (2) are: heating temperature 160°C, rotation speed 150r / min, and premixing time 40min.

[0054] In the following preferred embodiments, the reaction conditions of step (3) are: reaction temperature 150°C-200°C, reaction time 18-22 min. More preferably, the reaction temperature is 170°C, and the reaction time is 20 min.

[0055] Example 1

[0056] A phase-change thermal interface material with interface adaptability is prepared from the following raw materials: 100 g of a phase-change matrix premix, 5 g of dioxyborane maleimide, 3 g of bisdioxyborane, 0.1 g of dicumyl peroxide and 30 vol% of a thermally conductive filler (based on the total volume of the phase-change matrix premix, a grafting agent, a cross-linking agent and an initiator), the phase-change matrix premix comprises stearic acid and a polyolefin elastomer in a mass ratio of 7:3, and the thermally conductive filler comprises carbon fiber and aluminum nitride in a volume fraction ratio of 4:1.

[0057] The method for preparing the above-mentioned phase-change thermal interface material with interface adaptability comprises the following steps:

[0058] (1) drying aluminum nitride powder and carbon fiber powder and adding them into a stainless steel barrel for premixing;

[0059] (2) Stearic acid and polyolefin elastomer are added to a stainless steel barrel and premixed by heating in an oil bath at a temperature of 160° C., a rotation speed of 150 r / min, a premixing time of 40 min, and stirring;

[0060] (3) Add diisopropylbenzene peroxide and diborane maleimide to the stainless steel barrel in sequence, raise the temperature to a stable temperature of 170°C-200°C, mix and stir for 10 minutes, then add bis(diborane) to the stainless steel barrel, mix and stir at 170°C for 8 minutes, and after complete reaction, a phase change thermal interface material marked as SP5 is obtained.

[0061] Example 2

[0062] The same as Example 1, except that the amount of dioxyborane maleimide is 1 g and the amount of bisdioxyborane is 0.6 g. The obtained material is marked as SP1.

[0063] Example 3

[0064] The same as Example 1, except that the amount of dioxyborane maleimide is 2 g and the amount of bisdioxyborane is 1.2 g. The obtained material is labeled SP2.

[0065] Example 4

[0066] The same as Example 1, except that 3 g of dioxyborane maleimide and 1.8 g of bisdioxyborane were used. The obtained material was labeled SP3.

[0067] Example 5

[0068] The same as Example 1, except that the amount of dioxyborane maleimide was 4 g and the amount of bisdioxyborane was 2.4 g. The obtained material was labeled SP4.

[0069] Comparative Example 1

[0070] A phase-change thermal interface material with interface adaptability is prepared from the following raw materials: 100 g of a phase-change matrix premix, wherein the phase-change matrix premix comprises stearic acid and a polyolefin elastomer in a mass ratio of 7:3.

[0071] The preparation method of the above-mentioned phase change thermal interface material with interface adaptability includes the following steps: adding stearic acid and polyolefin elastomer into a stainless steel barrel and premixing them by heating in an oil bath, the heating temperature is 160°C, the rotation speed is 150r / min, the premixing time is 20min, and the phase change thermal interface material is obtained after stirring and reacting, and is marked as SP.

[0072] Comparative Example 2

[0073] A phase-change thermal interface material with interface adaptability is prepared from the following raw materials: 100 g of stearic acid.

[0074] The preparation method of the above-mentioned phase change thermal interface material with interface adaptability includes the following steps: adding stearic acid into a stainless steel barrel and premixing it in an oil bath, the heating temperature is 160°C, the rotation speed is 150r / min, and the mixing time is 20min to obtain a phase change thermal interface material marked as SA.

[0075] Comparative Example 3

[0076] The same as Example 1, except that the thermal conductive filler is 20 vol%.

[0077] Comparative Example 4

[0078] Same as Example 1, except that the thermal conductive filler is 10 vol%.

[0079] Comparative Example 5

[0080] Same as Example 1, except that the thermal conductive filler is 0 vol%.

[0081] The performance of the materials obtained in Examples 1-5 and Comparative Examples 1-5 was tested. Figure 1-8 shown.

[0082] from Figure 5 It can be seen that after Example 1 was broken and stored in an oven at 65°C for 5 hours, its fracture surface achieved self-adhesion, and the surface of the bonded sample was smooth. The sample can still be reloaded with a weight of 500g without any damage, which proves its repair performance. Figure 8 As can be seen, the print appears clearly on the sample and can be easily peeled off when heated. This further demonstrates that the excellent adaptability of the rough interface exhibited by SP5-30% greatly reduces the contact thermal resistance between devices.

[0083] Example 6

[0084] A phase-change thermal interface material with interface adaptability is prepared from the following raw materials: 100 g of a phase-change matrix premix, 8 g of dioxyborane maleimide, 4.8 g of bisdioxyborane, 0.5 g of dicumyl peroxide and 40 vol% of a thermally conductive filler, wherein the phase-change matrix premix comprises stearic acid and a polyolefin elastomer in a mass ratio of 6:4, and the thermally conductive filler comprises carbon fiber and aluminum nitride in a volume fraction ratio of 4:1.

[0085] The method for preparing the above-mentioned phase-change thermal interface material with interface adaptability comprises the following steps:

[0086] (1) drying aluminum nitride powder and carbon fiber powder and adding them into a stainless steel barrel for premixing;

[0087] (2) Stearic acid and polyolefin elastomer are added to a stainless steel barrel and premixed by heating in an oil bath at a heating temperature of 150° C., a rotation speed of 140 r / min, a premixing time of 80 min, and stirring;

[0088] (3) Diisopropyl peroxide and diborane maleimide were added to the stainless steel barrel in sequence, and the temperature was raised to a stable temperature of 150°C-170°C, and the mixture was stirred for 10 minutes. Then, bis(diborane) was added to the stainless steel barrel, and the mixture was stirred at 150°C for 12 minutes. After complete reaction, a phase change thermal interface material was obtained, which was labeled SP6.

[0089] Example 7

[0090] A phase-change thermal interface material with interface adaptability is prepared from the following raw materials: 100 g of a phase-change matrix premix, 6 g of dioxyborane maleimide, 3.6 g of bisdioxyborane, 0.2 g of dicumyl peroxide and 40 vol% of a thermally conductive filler, wherein the phase-change matrix premix comprises stearic acid and a polyolefin elastomer in a mass ratio of 8:2, and the thermally conductive filler comprises carbon fiber and aluminum nitride in a volume fraction ratio of 4:1.

[0091] The method for preparing the above-mentioned phase-change thermal interface material with interface adaptability comprises the following steps:

[0092] (1) drying aluminum nitride powder and carbon fiber powder and adding them into a stainless steel barrel for premixing;

[0093] (2) Stearic acid and polyolefin elastomer are added to a stainless steel barrel and premixed by heating in an oil bath at a temperature of 170° C., a rotation speed of 160 r / min, a premixing time of 30 min, and stirring;

[0094] (3) Diisopropyl peroxide and diborane maleimide were added to the stainless steel barrel in sequence, and the temperature was raised to a stable temperature of 170°C-200°C, and the mixture was stirred for 10 minutes. Then, diborane was added to the stainless steel barrel, and the mixture was stirred at 200°C for 8 minutes. After complete reaction, a phase change thermal interface material was obtained, which was labeled SP7.

[0095] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A phase change thermal interface material with interface adaptability, characterized in that: The invention is prepared from the following raw materials: a phase change matrix premix, a grafting agent, a crosslinking agent, an initiator and a thermal conductive filler. The phase change matrix premix comprises stearic acid and a polyolefin elastomer, and the mass ratio of stearic acid to the polyolefin elastomer is 6-8:2-4. The grafting agent is dioxyborane maleimide, and the crosslinking agent is bisdioxyborane.

2. The phase-change thermal interface material with interface adaptability according to claim 1, characterized in that: The invention comprises, by weight, 100 parts of a phase change matrix premix, 1-5 parts of a grafting agent, 0.6-3.0 parts of a crosslinking agent and 0.1-0.5 parts of an initiator.

3. The phase-change thermal interface material with interface adaptability according to claim 1 or 2, characterized in that: The mass ratio of the stearic acid to the polyolefin elastomer is 7:

3.

4. The phase-change thermal interface material with interface adaptability according to claim 1, characterized in that: Based on the total volume of the phase change matrix premix, the grafting agent, the crosslinking agent and the initiator, the volume of the thermal conductive filler is 0-40 vol% of the total volume.

5. The phase-change thermal interface material with interface adaptability according to claim 1 or 4, characterized in that: The thermal conductive filler comprises carbon fiber and aluminum nitride, and the volume fraction ratio of the carbon fiber to the aluminum nitride is 4:

1.

6. The phase-change thermal interface material with interface adaptability according to claim 1 or 2, characterized in that: Borane maleimide is prepared by the reaction of maleic anhydride, furan, 3-amino-1,2-propanediol and phenylboronic acid.

7. The phase-change thermal interface material with interface adaptability according to claim 1 or 2, characterized in that: The bisdioxyborane is prepared by the following steps: adding benzene-1,4-diboric acid and 1,2-propylene glycol to a mixed solvent of tetrahydrofuran and water, and then adding magnesium sulfate, and reacting at room temperature to obtain the bisdioxyborane.

8. The method for preparing a phase-change thermal interface material with interface adaptability according to any one of claims 1 to 7, characterized in that: The steps include: (1) adding the dried thermal conductive filler into a reaction container for premixing; (2) adding stearic acid and polyolefin elastomer to the premixed thermal conductive filler, heating and premixing, and stirring; (3) Adding an initiator, a grafting agent and a cross-linking agent into the reaction container in sequence, and obtaining a phase change thermal interface material after complete reaction.

9. The preparation method according to claim 8, characterized in that: The conditions for heating premixing in step (2) are: heating temperature 150° C.-170° C., rotation speed 140-160 r / min, and premixing time 30-80 min.

10. The preparation method according to claim 8, characterized in that: The reaction conditions of step (3) are: reaction temperature 150°C-200°C, reaction time 18-22 min.

Citation Information

Patent Citations

  • Polymer compositions comprising cross-linked polymers comprising boronic ester functions enabling exchange reactions, process for preparing them and their use

    CN108368206A

  • Phase change thermal interface material and preparation method thereof

    CN116622239A

Cited By

  • High-enthalpy-value flexible phase change material and preparation method and application thereof

    CN120290003A

  • High-enthalpy flexible phase change material, and preparation method and application thereof

    CN120290003B